Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les professions de la culture et des communications au Québec en 2021 - Lubin, Marc-Ancy (Institut de la statistique du Québec, 2024)
Keywords: Bibliographie; Nettoyer

Creative Control: The Ambivalence of Work in the Culture Industries - Siciliano, Michael L. (Creative Control, 2021)
Michael L. Siciliano draws on nearly two years of ethnographic research as a participant-observer in a Los Angeles music studio and a multichannel YouTube network to explore the contradictions of creative work. Creative Control explains why “cool” jobs help us understand how workers can participate in their own exploitation.
Keywords: Myriam; cognitive capitalism; creative labor; digital media; precarity; sociology of labor

Identity work in female-led creative businesses - Martin, Lynn; Jerrard, Bob; Wright, Lucy (Gender, Work & Organization, 2020)
This study explores the identity work carried out by three female owner-managers in creative industry businesses, identified in Government reports as a discriminatory industrial sector for women in the UK. Through the development of narratives by the owners and other participants, observation of practice and review of online and offline materials, three cases emerged. These showed overlapping, different identities developed and performed through identity work. Each presented rational and logical persona as business leaders despite observation showing extensive use of intuition and gut feeling in both creative and entrepreneurial aspects of the business. Intuition and gut feeling were seen as inappropriate at work as they belonged to the home sphere, emotionally based and therefore automatically unreliable. While occupying male stereotypes and avoiding the female realm of emotion at work, these women expressed femininity through their emphasis on the maternal, ‘being a good mother' as a desired ideal being embedded in work as well as home practice.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12357
Keywords: Myriam; creative industries; entrepreneurship; gender; identity; innovation